Electrical drives and controls - Gnanavadivel, J. (Anuradha, 2011)
The significance of this book is to provide a basic knowledge of electrical drives, motor characteristics, starting methods, conventional and solid state speed control of AC and DC drives. Each chapter contains two mark questions and answers, solved problems and review questions to get complete knowledge of the subject.